2017
DOI: 10.18632/oncotarget.16991
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of pyruvate dehydrogenase kinase-2 re-sensitizes paclitaxel-resistant human lung cancer cells to paclitaxel

Abstract: Despite impressive initial clinical responses, the majority of lung cancer patients treated with paclitaxel eventually develop resistance to the drug. Pyruvate dehydrogenase kinase-2 (PDK2) is a key regulator of glycolysis and oxidative phosphorylation, and its expression is increased in a variety of tumors. In this study, the role of PDK2 in mediating paclitaxel resistance in lung cancer cells was investigated using biochemical and isotopic tracing methods. Increased expression of PDK2 was observed in paclita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 27 publications
2
38
0
Order By: Relevance
“…Cisplatin-resistance has been linked to an increased dependence on glycolysis and pentose phosphate pathway [21,37,38]. Studies also showed that enhanced glycolysis is associated with paclitaxel resistance and that inhibition of glycolysis could reverse the drug resistance [39][40][41]. Along with these studies, our findings add to the evidence that aerobic glycolysis plays a significant role in determining clinical outcomes of paclitaxelcisplatin chemotherapy in NSCLC.…”
Section: Discussionsupporting
confidence: 70%
“…Cisplatin-resistance has been linked to an increased dependence on glycolysis and pentose phosphate pathway [21,37,38]. Studies also showed that enhanced glycolysis is associated with paclitaxel resistance and that inhibition of glycolysis could reverse the drug resistance [39][40][41]. Along with these studies, our findings add to the evidence that aerobic glycolysis plays a significant role in determining clinical outcomes of paclitaxelcisplatin chemotherapy in NSCLC.…”
Section: Discussionsupporting
confidence: 70%
“…By reducing the conversion of pyruvate to acetyl‐CoA, PDK2 switches carbon flow from the tricarboxylic acid cycle and de novo lipogenesis to lactate production, thus facilitating Warburg effect . Dysregulation of PDK2 is reported in multiple cancers, and linked to proliferation, metastasis, and chemoresistance of cancer cells . Specifically, in HCC, PDK2 is identified as target of miR‐214, and involved in disease progression .…”
Section: Discussionmentioning
confidence: 99%
“…33 Dysregulation of PDK2 is reported in multiple cancers, and linked to proliferation, metastasis, and chemoresistance of cancer cells. [34][35][36][37] Specifically, in HCC, PDK2 is identified as target of miR-214, and involved in disease progression. 37 Recently, PDK2 has been proved to be negatively regulated by miR-422a, and PDK2 inhibition by miR-422a results in increased activity of the pyruvate dehydrogenase and higher acetyl-CoA level.…”
Section: Discussionmentioning
confidence: 99%
“…Lung cancer cells that are resistant to carboplatin, which has a similar mode of action, are more dependent on glycolysis ( 106 ). In addition, paclitaxel-resistant lung cancer cells show higher expression of PDK2 as compared to their parental cells ( 105 ). As a result, these resistant cells are more dependent on glycolysis than OXPHOS and could be sensitized to paclitaxel through PDK2 inhibition.…”
Section: Metabolism and Drug Resistancementioning
confidence: 99%